Erosion And Sediment Yield Evaluation In Regards Of Erosion Sediment Control Practices (Escp) - Ismail, Siti Isma Hani (2010)

(untitled)
During construction, large areas of soil are exposed to the risk of water erosion due to earthworks activities. Bare slopes and drains choked with sediment can often be observed on construction sites. This erosion may result in a significant increase in sediment loads to receiving waters and the construction techniques used on site can cause offsite contamination. Erosion from the study area occurred due to the removal of the vegetation cover, high rainfall intensity and the failure of the sediment basins to function effectively. The present study aims to evaluate the erosion and sediment yield due to storm rainfall and runoff on a construction site located at Sungai Ara, Penang state of Malaysia. The soil loss was evaluated by using empirical erosion modelling namely the Revised Universal Soil Loss Equation (RUSLE), Modified Soil Loss Equation (MSLE) and Modified Universal Soil Loss Equation (MUSLE) and from the water samples taken at the study area. Results showed that large amount of sediment has being eroded from the study area. The highest annual erosion rates estimated is by using the RUSLE equation is recorded at Borehole 19 with soil loss of 7,772 tons/ha/y. By analyzing the samples collected at the Pond B, the TSS value is noted from 352 mg/l to 5031 mg/l at Inflow and 309 mg/l to 5375 mg/l at Outflow which fall under the Class V according to the classification by Department Of Environment in Malaysia. However, the results shows that the measured soil loss was very much smaller compared to the calculated soil loss.